1983
DOI: 10.2170/jjphysiol.33.485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium on the membrane activity and contraction of the circular muscle of rat myometrium during late pregnancy.

Abstract: Comparative effects of Mg were studied on circular muscle strips of pregnant rat myometrium near term and during delivery. Frequency and amplitude of spontaneous contraction were markedly depressed by adding 0.6 mM Mg to Mg-free Krebs solution in the muscle strips taken in the morning of Days 19 and 22 of pregnancy. Frequency decreased, whereas the amplitude was not depressed by 0.6 mM Mg in muscle strips taken during delivery. Plateau potential dominated in the circular muscle taken in the morning on Days 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1984
1984
1995
1995

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…In some preparations, the muscle strip underwent a persistent contracture. This feature strongly contrasted to that observed in the prepartum preparation (OSA and OGASAWARA, 1983).…”
contrasting
confidence: 91%
“…In some preparations, the muscle strip underwent a persistent contracture. This feature strongly contrasted to that observed in the prepartum preparation (OSA and OGASAWARA, 1983).…”
contrasting
confidence: 91%
“…Rather, these features suggest adrenergic effects tended to be transformed to those of the following days. In a previous report (OsA and OGASAWARA, 1983), it was shown that the contractile inhibition was caused by ap- Vol. 34, No.…”
Section: Discussionmentioning
confidence: 94%
“…It was recently reported (OsA and OGASAWARA, 1983) that the amplitude of contraction was markedly depressed by adding 0.6 mM Mg to Mg-free Krebs solution to the circular muscle strips taken in the morning on Day 22 of pregnancy, however it was not depressed in the circular muscle strips taken during delivery. The depressant effect of Mg on phasic contraction of the muscle strip taken in the morning on Day 22 was progressively decreased by prolonged perfusion with Mg-free Krebs solution.…”
mentioning
confidence: 93%
“…Moreover, calcium has been known to play a dual role in the electrical activity of uterine smooth muscle of small animals, one being an excitatory role in spike potential [3,4], and the other an inhibitory role in membrane sta bilization [3,5]. In human myometrium, spontaneous contractions were strongly affected by the concentration of external calcium; 2.5 mM ionic calcium in Krebs solu tion was the most efficient concentration and both ex cess and low ionic calcium levels suppressed contraction [6], On the other hand, the effect of external magnesium on spontaneous electrical and mechanical activities of the circular muscle of term pregnant rat uterus was investigated and it was indicated that the contractile depression was largely due to suppression of the plateau potential [7], In pregnant human myometrium, ionic magnesium suppressed spontaneous contractions, espe cially in frequency, by suppressing the gradient of pace maker potential and the duration of each action poten tial [8], As mentioned above, it is obvious that sponta neous contraction of the uterus is regulated by mem brane activity based on ionic currents. Furthermore, in rat myometrium, P-adrenergic action of catecholamine indicated that a hyperpolarization of the membrane due to an increase in membrane conductance [9,10] and an increase in cAMP [11] underlay the depression of spon taneous contraction, in which ionic calcium might play an important role.…”
Section: Introductionmentioning
confidence: 99%